Does innovation strategy affect financial, social and environmental performance? - Ferdaws Ezzi; Anis Jarboui (Journal of Economics, Finance and Administrative Science, 2016)
In the very study, the emphasis lays on the specific problem of analyzing the impact of the innovation strategy (in particular investment in research and development) on the financial, social and environmental performance. After discussing this subject theoretically, we propose our research hypotheses which, in turn, will be corroborated by an empirical study of 96 Tunisian companies. Indeed, the results are noteworthy and important to the extent that one can say that the innovation strategy has a crucial impact on the performance of the companies. – – El énfasis de este estudio recae sobre el problema específico del análisis del impacto de la estrategia de innovación (en concreto, las inversiones en investigación y desarrollo) sobre el rendimiento financiero, social y ambiental. Después de analizar este asunto desde el punto de vista teórico, se propone una hipótesis de investigación que, a su vez, deberá ser corroborada por un estudio empírico de 96 empresas tunecinas. De hecho, los resultados son destacados e importantes, y permiten decir que la estrategia de innovación tiene un impacto crucial en el rendimiento de las empresas.
Keywords: J20; 330; Innovation strategy; Social performance; Financial performance; Environmental performance; Estrategia de innovación; Rendimiento social; Rendimiento financiero; Rendimiento ambiental